Adherence To A Gender Responsive Pedagogy For Teaching And Learning In Secondary Schools In Temeke District, Tanzania - Erasto Losioki, Bertha (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Gender equality in pedagogy is important in ensuring good quality education. However, pedagogical issues and social cultural norms continue to impede the implementation of gender equality in teaching and learning in schools. This study focused on adherence to a gender responsive pedagogy for teaching and learning in secondary schools in Temeke District. Data were collected from 288 participants selected through random and purposive sampling. The study used both quantitative and qualitative approaches. In depth interview, questionnaire survey and non-participant observation methods were used to collect primary data, and documentary review was used to collect secondary data. Likert scale was used to measure gender equality adherence. Content analysis was used to analyse qualitative data according to key themes and research objectives. Data were presented in frequency tables and bar charts. Major findings show that gender equality is adhered to in school practices and a gender responsive pedagogy is adequately adhered to in the teaching and learning process. Three quarter of the respondents show that the curriculum addresses gender equality in school practice including teaching and learning in the classroom. This study recommends that the Ministry of Education Science and Technology in collaboration with education stakeholders should continue to emphasize the implementation of a gender responsive pedagogy in teaching and learning practice in schools and to raise awareness on gender equality issues at the community level.